(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2010)
Some new nomenclature combinations in Achillea L., Buglossoides Moench, Lotus L., Pseudolisymachion Opiz, Pulsatilla Mill. та Ranunculus L. are proposed.